Using the Retrobulbar Spot Sign to Assist in Diagnosis and Management of Central Retinal Artery Occlusions. (22nd June 2019) - Smith, Austin T.; Wilbert, Christopher D.; Ferre, Robinson M.
Abstract : Point‐of‐care ultrasound has become an integral part of the evaluation of monocular vision loss. Most commonly, it has been used to evaluate retinal detachment, vitreous hemorrhage, and posterior vitreous detachment. Point‐of‐care ultrasound can also be used to evaluate central retinal arterial occlusion, whereby a retrobulbar spot sign is present. We present a case series of 4 patients presenting with monocular vision loss who were found to have central retinal artery occlusion. We describe what a retrobulbar spot sign is and how its presence or absence can assist in the evaluation and treatment of these patients.